Sosialisasi Digital Marketing Melalui Konten Sosial Media Sebagai Upaya Menumbuhkan Minat Wirausaha Siswa MA Assa’adah Bungah - Fatihatus Sahliyah; Nur Fadhillah; Achmad Fahim (TAAWUN, 2024)
The purpose of this program is to increase student’s understanding of digital marketing, and using social media content in digital marketing strategy. This event was held in the form of socialization and training on creating Instagram content as a marketing tool. The socialization was carried out in the form of an interactive seminar, presentation and followed by a question and answer session regarding the material that had been presented. And then continued with training on creating Instagram content using the Canva application. As an evaluation, the team provides a post-test in the form of direct practice in creating content using their smartphone as well as conveying obstacles and finding a solution. The result of this event showed that 95% of participants understood the digital marketing material presented, indicated by the changes in knowledge and skills after participating in this event. With this event, hope that the students can utilize and maximize their potential to start entrepreneurship and foster the spirit of young entrepreneurs through digital as a marketing tool.